Laminar Entry Flow of Herschel-Bulkley Fluids in a Circular Pipe - GUPTA, R. C. (Institutional Knowledge at Singapore Management University, 2000)
Fargie and Martin used an elegant approach to obtain the entry region flow of Newtonian fluids in a circular pipe. They combined the differential and integral momentum equation in such a way that elimination of pressure gradient leads to a closed form solution. In this paper we extend this procedure to study the laminar entry region flow of Herschel-Bulkley fluids in a circular pipe. The solution procedure involves certain approximations. Applicability of these approximations to Herschel-Bulkley fluids has been discussed and the flow description has been obtained for various values of the flow behavior index and the Herschel-Bulkley number. Results have been illustrated graphically and compared with other available solutions: momentum integral and momentum energy integral solutions of the problem. Data displayed in the paper should be useful for design of any flow intake device involving Herschel-Bulkley fluids.